Model of a competency-based learning assessment system for the health programme of the Universidad Nacional del Santa - Beltrán-Osorio, Rafael Roberto (2024)
Objetive: To establish a model of learning evaluation system to ensure the development of those established in the curriculum of the human medicine program of the Universidad Nacional del Santa. Methods: The methodology used was basic, descriptive and quantitative, and the instrument used was a questionnaire, which was applied to a sample of 179 medical students and 76 teachers. Data collection was performed with informed consent through an online Google form, which included 30 items, based on 4 stages: evaluation planning, evaluation stage, evaluation techniques and instruments, and evaluation system model. The SPSS v25 statistical program was used to process and validate the data and make the variable matrix, obtaining a Cronbach's alpha of 0.946. Results: 48.0% of students state that they are almost always informed about the study plan. Likewise, 33.0% of students mentioned that sometimes the syllabus is available and discussed at the beginning of the course. In addition, 48.0% of students consider that the evaluation guides are almost always coherent with the learning competencies. Conclusion: The learning assessment system model designed ensures alignment with the competencies established in the curriculum of the human medicine program at the Universidad Nacional del Santa. This model integrates coherent planning, effective diagnostic and formative stages, and diversified techniques and instruments, promoting a competency-based approach. In addition, it promotes the combination of traditional and alternative methods, strengthening feedback and continuous learning. Its implementation seeks to improve educational quality and guarantee the achievement of professional competencies required in medical training.